To determine the equivalence of the two expressions that Ella worked with, let’s first rewrite each expression clearly:
-
The first expression:
\( 5f + 3.65(1) + 3.65 + 3.68 \)
Simplifying this:
\( 3.65(1) \) is just \( 3.65 \), so the expression becomes:
\( 5f + 3.65 + 3.65 + 3.68 = 5f + 7.3 + 3.68 = 5f + 7.3 + 3.68 \).
Therefore, it simplifies to:
\( 5f + 7.3 + 3.68 = 5f + 11.38 \). -
The second expression:
\( 6f + 2.6(6) + 2.6 + 8.6 \)
We can rewrite \( 2.6(6) \) as \( 15.6 \), so:
\( 6f + 15.6 + 2.6 + 8.6 = 6f + 15.6 + 2.6 + 8.6 = 6f + 26.8 \).
Now we have:
- First expression: \( 5f + 11.38 \)
- Second expression: \( 6f + 26.8 \)
To establish whether they are equivalent, we can check by substituting a value for \( f \) (in this case, let's use 1):
- For \( f = 1 \):
-
First expression:
\( 5(1) + 11.38 = 5 + 11.38 = 16.38 \) -
Second expression:
\( 6(1) + 26.8 = 6 + 26.8 = 32.8 \)
-
Since \( 16.38 \neq 32.8 \), this shows different results for the same input value (in this case, \( f = 1 \)). Thus, we can conclude:
The expressions are not equivalent because Ella would get different results when substituting different numbers for \( f \).
So, the correct response is:
The expressions are not equivalent because Ella would get different results when substituting different numbers for f.